Natureza, trabalho e representaçõs sociais : os pescadores profissionais de Porto Rico (Estado do Paraná, Brasil) entre as transformações e as permanências - Sponchiado, Dirlene (2011)
This study focused on analyzing the major transformations in the social representations about nature and work prepared by professional fishermen of Puerto Rico between the years 1994 to 2009 which had already been recorded in previous studies. Besides pointing out the changes and continuities in social representations, we tried to understand the processes (social, economic, political, environmental) that acted up and work on those representations, and especially the fishermen's participation, either as staff or as influenced by those changes. To achieve these objectives, this study was divided into four tracks: methodological, theoretical, historical and social representations elaborated by the fishermen. For the first, we used the Qualitative Research method, based on Fernando Gonzalez Rey's Qualitative Epistemology. This line of thinking is characterized by a dialogic and interactive character, reality construction and interpretation and attention to the uniqueness in the knowledge production. In the second, we presented, through the theoretical framework proposed by Serge Moscovici and reworked by others, how the social representation phenomena construction occurs. For this, the path chosen was to approach reality as a construction of subjects living in society. In the third, we described the history of the region and Puerto Rico City to understand the transformation from one context to another, that influenced the fishermen's conceptions of work and nature. In the fourth and last, we tried, through the previous studies, to describe which the fishermen social representations of nature and work were. As we finished these trajectories, we made the analysis and discussion from the material described and pointed out that the economic, political and environmental changes required learning and using new strategies for survival. Nature and work representations shared by these fishermen have changed gradually, and the intensity of change is inversely proportional to the resistance that fishermen exert so that they do not change. The concept of nature remains very close to the initial, cognitively and affectively, in all of them. The social work representations are changing because the work is the practical part, the survival one, and it was necessary they would adapt them more quickly. The fishermen relation with nature and work have changed, but they are also trying to maintain or readjust their Social Representations, in order not to change who they are, or who they would like to be. Fishermen affected by the processes, are also active participants in the (re)construction of reality in which they live. We believe that, even active, professional artisanal fishermen are gradually disappearing, and today's fishermen can be considered the last remaining. Along with a group extinction process we are also losing a culture and history.